Aligning State Finance Regulations with SOE Bankruptcy Policy: Evidence from the United States - Waluyo, Waluyo; Tegnan , Hilaire; Setiowati , Noni Oktiana (Lembaga Contrarius Indonesia, 2025)
Existing regulations governing the execution of state-owned enterprise (SOE) assets in Indonesia lack coherence, resulting in legal uncertainty and inconsistencies between state financial policies and bankruptcy laws. This misalignment is evident in the conflicting interpretations of Constitutional Court Decisions No. 48/PUU-XI/2013 and No. 62/PUU-XI/2013, as well as contradictions among the State Finance Law, State Treasury Law, State-Owned Enterprises Law, and Bankruptcy Law. This study aims to examine these regulatory uncertainties and propose solutions that promote legal certainty and justice. This research adopts a normative legal methodology, utilizing a legislative approach and comparative analysis, with a particular focus on the United States as a reference model. The study draws on primary and secondary legal sources, which are analyzed using a deductive method. The findings highlight three key aspects: first, there is significant disharmony within Indonesia’s financial and bankruptcy regulations concerning SOEs. Second, in contrast, the United States provides a more structured bankruptcy framework that facilitates business resolution while allowing for government intervention in cases where bankruptcy poses a systemic risk. Third, the study presents several policy recommendations to align Indonesia’s state financial and bankruptcy regulations with those governing SOEs, ensuring a more coherent and just legal framework. The findings of this study suggest that the Indonesian government should consider these recommendations to enhance policy frameworks for executing SOE assets, particularly within Limited Liability Company, thereby ensuring a balance between financial accountability and economic stability.